Research Competencies and its Relationship with the Scientific Production of University Teachers in Peru - Suyo-Vega, Josefina Amanda; Meneses-La-Riva, Mónica Elisa; Fernández-Bedoya, VÃctor Hugo (International Journal for Educational and Vocational Studies, 2020)
Teaching research at a university becomes important because it reflects the quality of the academic institution, this quality is measured through scientific production, which is product of teaching and research experience. The objective of this investigation was to determinate the relationship of research competencies and scientific production university teachers in several institutions located in Peru. The methodology developed was of quantitative approach, correlational level, non-experimental design; two instruments were applied to 205 teachers who taught courses related to research competencies. The first variable, research competencies, had three dimensions: development of research projects, methodology of research projects, and use of APA style, constructed and validated previously by Ceballos and Tobón. The second variable, scientific production, whose authors were Rodríguez and Rivas it consisted of four dimensions: project training, training in scientific publication and dissemination, project implementation and scientific visibility. The questionnaire contained of 21 items, whose valuations were through the frequency Likert scale (1=never, 2=rarely, 3=occasionally, 4=frequently, and 5=very frequently). Spearman’s rho determinate a high ratio (r=0.788) correlation between the two variables (research competencies and scientific production). The dimensions of research competencies were also correlated with the main variable scientific production, finding that development of research projects, methodology of research projects, and use of APA style have a positive relation (r=0.702; 0.821 and 0.658). The main conclusion is that teachers who are in charge of research courses have greater possibilities of having scientific production, such as publishing scientific articles in indexed journals, but there is a flaw that predominates this group over the application of the APA Style Standards, suggesting the need to develop workshops for writing scientific articles.